2018
DOI: 10.1007/s10903-018-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Self-Rated Morbidities Among South Asian Migrant Gas Station Workers in Kuwait

Abstract: Gas station workers (GSWs) are at elevated risk of morbidities associated with exposure to petrochemical substances. This cross-sectional study assessed the prevalence and examined demographics and occupation-related risk factors associated with self-rated ill-health among GSWs in Kuwait. Structured questionnaire was used to record self-rated ill-health from 460 selected GSWs of South-Asian origin. Prevalence of self-rated ill-health conditions was computed. Random-intercept multivariable logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A long‐distance bus station generally includes a station hall, a platform, and other areas. Except for the outdoor platform, the remainder of the space is a typical indoor area, which has the risk of inducing architecture‐related diseases 23‐28 . We were focused on the relationship between indoor environmental factors of long‐distance bus stations and AR of their employees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long‐distance bus station generally includes a station hall, a platform, and other areas. Except for the outdoor platform, the remainder of the space is a typical indoor area, which has the risk of inducing architecture‐related diseases 23‐28 . We were focused on the relationship between indoor environmental factors of long‐distance bus stations and AR of their employees.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the outdoor platform, the remainder of the space is a typical indoor area, which has the risk of inducing architecture-related diseases. [23][24][25][26][27][28] We were focused on the relationship between indoor environmental factors of long-distance bus stations and AR of their employees. The indoor spaces of 226 long-distance bus stations, each having a total area of more than 1000 m 2 , were considered as the study objects.…”
mentioning
confidence: 99%
“…Khadadah et al showed that the prevalence of asthma was 15% among Kuwaiti adults (93,923), the figure we have used, and 18% among children (70,158) [ 38 ]. The prevalence of asthma (actually shortness of breath assumed to be asthma) among immigrants is much lower, as described by Al-ayyadhi—around 7.6% [ 39 ]. We have therefore estimated the total asthma prevalence to be about 315,473 adults or 9.5% of the adult population overall.…”
Section: Resultsmentioning
confidence: 99%
“…The term “migrant worker” has also been used to refer to natives moving within a large ethnically and culturally diverse country, perhaps from the countryside to the town (Al-Ayyadhi and Akhtar 2018 ; Fan and Qian 2017 ; Zeng et al 2014 ). Such internal migrants may or may not experience language and cultural differences; however, if they do, they would be in a comparable situation to many international migrants (Bergbom and Vartia 2021 ).…”
Section: Heterogeneity and Lack Of Definition For “Migrant” In Researchmentioning
confidence: 99%